(untitled) (CIPEEX, 2023)
In the absence of vision, postural control requires compensatory mechanisms to be maintained effectively. The objective of this study was to identify the differences in postural control between visually impaired children and adults. Blind individuals participated in the study, divided into two groups: DV children group (8 children; both sexes; average age 8.8±2); DV adults group (6 adults; both sexes; average age 37.5±6). To evaluate postural control, the SMART-D 140® System with two Kistler model 9286BA force platforms was used, allowing the analysis of center of pressure (CoP) oscillations. The participants were instructed to stand in an orthostatic position, with their arms close to their bodies for 30 seconds, with their eyes open and closed, with and without proprioceptive perturbation. For proprioceptive alteration, a 5cm high foam was used on the force platform. According to the median values of the group’s COP parameters. According to Mann-Whitney, the main differences were found in the M/L COP and COP velocity, where we observed that regardless of the condition, blind adults sway more than blind children with a large effect size (r = 0.82). Interestingly, even when challenging the sensory system, we did not find a significant difference in either group (p > 0.05). Our findings corroborate those described by other authors who state that the process of balance control in children does not involve vision due to insufficiently developed visuomotor coordination.